Someone help me on this.
![Someone help me on this class=](https://us-static.z-dn.net/files/d23/e122cc750aadf3ef11f738a2479326f4.jpg)
Answer:
[tex]-57-39i[/tex]
Step-by-step explanation:
So we have the expression:
[tex](7+2i)(-9-3i)[/tex]
FOIL:
[tex]=7(-9)+7(-3i)+2i(-9)+2i(-3i)[/tex]
Simplify:
[tex]=-63-21i-18i-6i^2[/tex]
Recall that i² is just -1. Thus:
[tex]=-63-21i-18i-6(-1)[/tex]
Simplify:
[tex]=-63-21i-18i+6[/tex]
Combine like terms:
[tex]=(-63+6)+(-21i-18i)[/tex]
Add:
[tex]=-57-39i[/tex]
And we're done!